Case report: Acute toxic myocardial damage caused by 5-fluorouracil—from enigma to success - Lasica, Ratko; Spasic, Jelena; Djukanovic, Lazar; Trifunovic-Zamaklar, Danijela; Orlic, Dejan; Nedeljkovic-Arsenovic, Olga; Asanin, Milika (Frontiers in Cardiovascular Medicine, 2022)
Considering the pandemic of both cardiovascular diseases and oncological diseases, there is an increasing need for the use of chemotherapy, which through various pathophysiological mechanisms leads to damage to heart function. Cardio toxicity of chemotherapy drugs can manifest itself in a variety of clinical manifestations, which is why establishing a valid diagnosis is a real mystery for clinicians. Acute systolic heart failure (AHF) due to the use of 5-fluorouracil (5-FU) is a rare occurrence if it is not associated with myocardial infarction, myocarditis or Takotsubo cardiomyopathy. Therefore, we decided to present a case of an 52-year-old male who was diagnosed with stage IV RAS wild-type adenocarcinoma of the rectum and in whom the direct toxic effect 5-FU is the main reason for the appearance of toxic cardiomyopathy.